Reliability of inverse dynamics of the whole body in the tennis forehand - Iino, Y.; Kojima, T. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Reliability of joint moment calculation using inverse dynamics is critical for evaluation of joint function and has been investigated for locomotion and lifting tasks, but not for sport movements in which the trunk can not be assumed to be rigid. The tennis forehand was studied in this paper because many biomechanical studies on the movement have been performed (Elliott et al., 1989) and the trunk twists substantially in the forehand. The purpose of this study was to investigate the reliability of the inverse dynamic analysis of the whole body in a tennis forehand using different segment inertial parameter (SIP) sets.